A case of systemic lupus erythematosus presenting with protein-losing enteropathy - Nuran TÜRKÇAPAR; Nil ÖZYÜNCÜ; Kubilay ÇINAR; Arzu ENSARİ and Özlem KÜÇÜK and Ramazan İDİLMAN and Neval DUMAN and Ali ÖZDEN (Turkish Journal of Gastroenterology, 2019)
-